E. coli Fermentation for the Production of Sialic Acid - Zhi, Li (Université d'Ottawa / University of Ottawa, 2014)
Sialic acid is the terminal sugar found on most glycoproteins and is crucial in determining serum half-life and immunogenicity on glycoproteins. The scarce supply of sialic acid hinders its advancement in basic research, diagnostic development and therapeutic production. In this work, the recombinant E. coli BRL04 (pBRL89) producing sialic acid was studied by some batch and fed batch runs of high cell density cultivation using a 3-L fermentor. Some cultivation conditions including carbon source, induction time, dissolved oxygen were optimized and different feeding strategies were compared to enhance sialic acid production. The results may be helpful to the further scale-up of sialic acid production and the production of other recombinant proteins by high cell density cultivation of E. coli.
Keywords: sialic acid; Escherichia coli; Feeding strategies